BIODEGRADABILITY: FLOATING ON THE SURFACE OF CULTURE - Zucker, Lisa (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1992)
A study of the work of Charlotte Salomon as an example of revolutionary feminist poetic practice.